(3eNJUQ GdTjN Ndjds - (3GdTjN Ndjd , VjGA GdOjf,J (B776 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Ndjd Hf ESMGb GdeGdcj GdMeO ddg MeOkG jhGaj eG JRGjO ef GdfYe hGdTcQ dg Ydi eG ChdGfG ef GdaVd hGdcQe s
(3BNQgG (B:s
(3ChMUd MjV Ch efj adGCTcGd hHGddg GdJhajb Je GdcJGH GdoeHGQc HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: 19s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B113s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1628s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdeGdcjs